Oferta de crédito rural, Segurança Alimentar e Produção de Alimentos. - Canavez, Geraldo Flávio (2009)
This dissertation accomplished an analytic study on the offer of the rural credit for the financing of food production. Its objective was to analyze the need to use the rural credit to subsidize the food production in Brazil, under the alimentary safety's perspective. The research collected information starting from temporary series obtained within official institutions about the international and national food crisis, the rural credit and the food production in Brazil, with emphasis to the production of rice, bean, corn, soy and wheat, component grains on a basic basket. It was used as a background for data analysation the theory of Malthus, The results show the importance of the rural credit and the need of adopting stronger measures, in the sense of fomenting this as a way of promoting the food production which not only is it a contribution with the alimentary safety's subject but also a important source of employment generation. The results also show the need of providing for the whole chain of production of grains the necessary information to access the several financing sources. It concludes that besides the alimentary safety's aspect for the country's development politics being a crucial factor, there is no way of dissociating the subject of the world hunger and of the hunger in Brazil. There is also no way to do it without credit politics to finance the production of grains in the necessary amount to provide the minimum of the needs of the population.